Evaluation of banana commercial micropropagation - Pedroso de Oliveira, Roberto; de Oliveira e Silva, Sebastião (Pesquisa Agropecuaria Brasileira, 1997)
The efficiency of a commercial micropropagation system of the Nanicão and Grand Naine triploid banana cultivars was evaluated. The in vitro culture was established in MS medium, supplemented with 30 g/L of sucrose and 0.18% of PhytagelTM, pH 5.7; bud multiplication was carried out in the same medium supplemented with 4.0 mg/L of BAP (benzilaminopurine). Plantlets were rooted in MS medium containing half the concentration of salts and supplemented with 30 g/L of sucrose and lacking growth regulators. After rooting, the plantlets were acclimatized in a green-house. Losses by contamination during the period of the in vitro establishment were 18.0% and 40.6% for cultivars Nanicão and Grand Naine, respectively. Average multiplication rates in the subcultures were 2.1 for 'Nanicão' and 2.4 for 'Grand Naine'. Two percent of the plantlets were lost during acclimation process. The average production of plantlets were 189.2 for 'Nanicão' and 198.8 for Grand Naine.